The Influence of Building Surroundings and Glass Cover in Bird Collisions - Amanda Cristina Lopes; Gustavo Oliveira Cotta Rocha; Marcela Fortes de Oliveira Passos; Luciana Barçante; Cristiano Schetini de Azevedo (Birds)
The characteristics of building surroundings can influence the number of bird deaths caused by collisions with glass structures. Thus, this study investigated whether the number of trees, the distance to the nearest tree, the number of fruit trees, and the glass area influenced the number of bird collisions on a university campus in Brazil from March 2017 (breeding and non-breeding seasons) to January 2018 (breeding season). Twenty-four birds died due to collisions with the windows in the one-year sampling. Among the factors evaluated, the number of trees and the area of the glass predicted the number of deaths from collisions. The greater the number of trees and the glass area, the greater the number of bird collisions. This suggests that the more vegetation there is near windows, the more birds are attracted, and the less visible the glass barrier becomes, possibly due to the appearance of trees in reflections or scenes viewed through the glass, making it difficult for birds to distinguish the real landscape from the reflected environment. If large expanses of glass are placed on buildings near vegetation, including trees, more bird collisions will occur. Thus, to reduce bird collisions, building designs should reduce the amount of glass used on building exteriors near vegetation and ensure the glass is treated with visual markers.